Effect of Y-Radiation on Chives Safety and Quality - Zuniga-Navarro, G; Ganga-Munoz, M; Junqueira-Conceicao Goncalve, M (2012)
The effect of ?-irradiation on the quality of chives was evaluated. The samples were irradiated at 1.0 and 2.0 kGy, stored at 4 °C for 10 days and used for microbiological (aerobic mesophilic, moulds and yeasts, E. coli and Salmonella sp), biochemical (vitamin C and lipoperoxide (MDA) contents and superoxide dismutase (SOD) and guaiacol peroxidase (POX) activity) and sensorial evaluation. For irradiated samples, the total counts of aerobic mesophilic and moulds and yeasts showed a reduction of 6 log cycles during storage, and colour analysis showed no significant difference (P > 0.05) for the b*-value. The contents of vitamin C were not significantly affected by irradiation and storage time. The MDA contents and SOD activity changed insignificantly at both ?-irradiation levels after storage, while POX was significantly increased (P ? 0.05) at 1 kGy. Samples irradiated at 2.0 kGy presented sensorial acceptance after the storage. These results show that ?-irradiation increases the shelf life of chives without significant changes in their quality. © 2012 The Authors. International Journal of Food Science and Technology © 2012 Institute of Food Science and Technology.